ANALYSIS OF THE MUDHARABAH CONTRACT AND ITS RECORDING FROM THE PERSPECTIVE OF SHARIA ACCOUNTING - Francisca Olivine Wardiyanti; Nur Imam Saifuloh (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2024)
This study analyzes the mudharabah contract and its financial recording from the perspective of sharia accounting. Mudharabah is a key financing contract in Islamic financial institutions, where the fund owner (shahibul maal) provides capital, while the fund manager (mudharib) manages the business activities. In Indonesia, the recording of mudharabah transactions must comply with PSAK 105 (Sharia Financial Accounting Standards), which regulates recognition, measurement, presentation, and disclosure of mudharabah transactions. This study uses a descriptive qualitative method, supported by literature review and analysis of sharia accounting practices. Findings show that proper recording and documentation are essential to ensure transparency and compliance with Islamic principles. The study also highlights challenges in aligning practical mudharabah implementation with PSAK 105 requirements. This research contributes to a better understanding of sharia accounting standards for mudharabah financing.